The dirty dozen [videorecording (DVD)] - Aldrich, Robert, 1918-1983; Marvin, Lee; Borgnine, Ernest, 1917-2012; Bronson, Charles, 1921-2003; Savalas, Telly, 1924-1994; Sutherland, Donald, 1935-; Cassavetes, John, 1929-1989; Nathanson, E. M., 1928-2016 (Warner Home Video, 2000)
A World War II drama in which an army major selects 12 men convicted for crimes of violence and offers them their freedom if they will complete a dangerous mission behind Nazi lines.